Open Networked "i-Learning" Models and Cases of "Next-Gen" Learning - Elia, Gianluca.; Poce, Antonella. (Springer US : Imprint: Springer, 2010)
A new overall interdisciplinary framework called i learning integrates managerial organization and technology aspects also known as technology enhanced learning . Open Networked "i Learning": Models and Cases of Next-Gen Learning begins its investigation with the important changes that have recently occurred within the management, technology and society fields. Social and cultural aspects of society that influence the dynamics and the styles of the learning processes are presented as well. The last section of this edited volume focuses on possible future scenarios of the learning processes by describing the main models, processes, tools, technologies, and involved organizations. About this book: The first available book that specifically focuses on i Learning . Includes descriptive case studies that describe how the i-Learning framework has been instanced and implemented. Presents social and cultural aspects of society that influence the dynamics and the styles of the learning processes. Open Networked "i Learning": Models and Cases of Next-Gen Learning is suitable for advanced under- and graduate level students and professors concentrating on computer science, engineering and business management as a secondary text or reference book. Professionals and researchers who work in the related industry of technology enhanced learning will find this book useful as well.